Capitalism and inequality what the right and the left get wrong - Muller, Jerry Z. (2013)
Argues that inequality is an inevitable product of capitalist activity, and expanding equality of opportunity only increases it, since some individuals and communities are simply better able than others to exploit the opportunities for development and advancement that capitalism affords. Cautions that despite what many on the right may think, that this is a problem for everybody, not just those who are doing poorly or those who are ideologically committed to egalitarianism; because if left unaddressed, rising inequality and economic insecurity can erode social order and generate a populist backlash against the capitalist system at large.